Impact of Momentum Index on Technical Analysis and Common Stock Pricing - Mahmood, Ahmed Abed (International Journal of Indonesian Business Review, 2025)
Purpose – For many international organizations, the phenomenon of variation has become a basis in the pricing of common stocks, as it has witnessed great developments over the past years because of the technological, economic, and health developments that have recently taken place in the world. Based on the integrated database of some Iraqi companies listed on the Iraqi Stock Exchange, a study aims to analyse stock price trends using the financial and technical tools of different sectors operating in Iraq. Methodology/approach – An analytical cognitive framework for the nature of these trends and their impact on the pricing of common stocks has been found by identifying the best analysis index that serves Iraqi securities investors and compressing the risks resulting from that investment to the maximum extent. This is done by relying on the Momentum Index. In addition to the analysis of the reciprocal relationship between the two study variables for the period from 2018–2020, using the test of the relationship between the variables and statistically and quantitatively analysing them, the study problem was interpreted. Findings – The major conclusion in this study is the ability Momentum Index to determine investors’ views on the fair price of shares. In addition, the study concluded a set of recommendations; the most important one is adopting the Momentum Index for its ability to predict the direction of the stock prices of companies and its ability to show the signals of selling and buying the shares of those companies, which positively reflects on the stock returns. Novelty/value – This study highlights the unique role of the momentum index in technical analysis and stock pricing, offering fresh insights to improve investment strategies.